Traumatic bilateral scaphoid fractures - Dariush Ghargozloo; Alessandro Tomarchio; Mauro Ballerini; Gianpaolo Chitoni (Medicinski glasnik, 2020)
Aim: To illustrate the surgical treatment of bilateral post-traumatic scaphoid fracture. Methods: We came across a young student, who sustained bilateral, undisplaced scaphoid waist fractures following a fall during a football match. Despite careful clinical and radiographic evaluation by four views at the Accident and Emergency (A&E) Department, we initially performed only the diagnosis of the left scaphoid fracture treating it with a percutaneous Acutrack headless screw. Eight months later this patient returned to the A&E department due to a new trauma to his right wrist with the onset of painful symptoms: cystic scaphoid non-union. No pain had been reported on the wrist in those months. Results: We performed osteosynthesis with Herbert headless screw through an extended volar approach placing a non-vascularized cortico-spongious bone grafts taken from radius. Periodic follow up by clinical examination, X-ray and CT scan with evidence of bone healing was performed. Conclusion: Bilateral scaphoid fractures are rarely encountered, mostly as stress fractures in athletes and manual workers. If left untreated, arthritis, deformity, and instability can lead to significant disability. Comprehensive imaging should be done in case of suspected scaphoid fractures, especially after a trauma, even in the presence of modest symptoms, as failure to do so may lead to missed fracture. Considering what was exposed, the radiographic check on the right wrist repeated about two weeks after the trauma would have avoided a missed diagnosis, even in the absence of reported clinical symptoms. We therefore recommend to repeat the radiographic examination in all situations like these.
Keywords: bone screws; carpal bones; delayed diagnosis; osteosynthesis; scaphoid bone